2015
DOI: 10.1128/mcb.01307-14
|View full text |Cite
|
Sign up to set email alerts
|

HSP105 Recruits Protein Phosphatase 2A To Dephosphorylate β-Catenin

Abstract: The Wnt/␤-catenin pathway causes accumulation of ␤-catenin in the cytoplasm and its subsequent translocation into the nucleus to initiate the transcription of the target genes. Without Wnt stimulation, ␤-catenin forms a complex with axin (axis inhibitor), adenomatous polyposis coli (APC), casein kinase 1␣ (CK1␣), and glycogen synthase kinase 3␤ (GSK3␤) and undergoes phosphorylation-dependent ubiquitination. Phosphatases, such as protein phosphatase 2A (PP2A), interestingly, also are components of this degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
2
48
0
Order By: Relevance
“…PP2A is composed of a core catalytic subunit (PPP2CA), a structural subunit (PR65/A) and variable regulatory B subunits (Janssens and Goris, ). A consistent finding across numerous studies is that PP2A dephosphorylates β‐catenin to prevent its ubiquitination and support the Wnt activation pathway (Su et al, ; Zhang et al, ; Yu et al, ). In the first model, PP2A‐mediated dephosphorylation of the APC 20R region was proposed to mark the end of a destruction complex cycle, allowing phosphorylated β‐catenin to leave the complex and so initiate a new round of β‐catenin modifications (Xu and Kimelman, ).…”
Section: Regulation By Dephosphorylationsupporting
confidence: 55%
See 1 more Smart Citation
“…PP2A is composed of a core catalytic subunit (PPP2CA), a structural subunit (PR65/A) and variable regulatory B subunits (Janssens and Goris, ). A consistent finding across numerous studies is that PP2A dephosphorylates β‐catenin to prevent its ubiquitination and support the Wnt activation pathway (Su et al, ; Zhang et al, ; Yu et al, ). In the first model, PP2A‐mediated dephosphorylation of the APC 20R region was proposed to mark the end of a destruction complex cycle, allowing phosphorylated β‐catenin to leave the complex and so initiate a new round of β‐catenin modifications (Xu and Kimelman, ).…”
Section: Regulation By Dephosphorylationsupporting
confidence: 55%
“…PP1 interacts with axin (Luo et al, ), while PP2A was reported to bind both axin and APC (Hsu et al, ; Seeling et al, ; Yamamoto et al, ). Of note, PP2A binding to axin might be indirect, involving the heat shock protein 70 (HSP70) family member HSP105 (Yu et al, ). PP2A is composed of a core catalytic subunit (PPP2CA), a structural subunit (PR65/A) and variable regulatory B subunits (Janssens and Goris, ).…”
Section: Regulation By Dephosphorylationmentioning
confidence: 99%
“…Colon cancer cells in which HSP110 has been shRNA-mediated and knocked down hardly proliferate, but proliferation is reactivated by the re-expression of HSP110 in these cells. Tumors from patients with high levels of HSP110 show high STAT3 phosphorylation levels and strong expression of proliferation markers [154,156]. Therefore, both the protein homeostasis function and the role of HSP110 on proliferative pathways may explain why this protein is linked to aggressive tumors.…”
Section: Hsp110 Functionsmentioning
confidence: 99%
“…Conversely, HSP110β can induce HSP70 expression through STAT3 in mammalian cells (Figure 4) [153]. It is now clearly established that HSP110 favors several signaling pathways, including the Wnt/β-Catenin, MyD88/TLR, and STAT3 pathways [154,155]. Localization and described functions of HSP110 and HSP70 within the STAT3 and STAT5 signaling pathways.…”
Section: Hsp110 Functionsmentioning
confidence: 99%
“…Hsp110 has been observed to participate in Wnt-mediated proliferation. Knockdown of Hsp110 results in degradation of β-catenin and inhibition of proliferation in colon cancer cell lines [85].…”
Section: Hsp110mentioning
confidence: 99%